Catlet scoring system as a new predictor for in-stent restenosis in patients with chronic coronary artery disease undergoing percutaneous coronary intervention with drug-eluting stent - Juan Wang; Mingchao Zhang; Weipeng Gan; Mingxing Xu; JiaYan Zhou; Lingfei Yang; Yongsheng Ke (Journal of Cardiothoracic Surgery)
Abstract Background He’s team have recently developed a new Coronary Artery Tree description and Lesion EvaluaTion (CatLet) angiographic scoring system, which is capable of accounting for the variability in coronary anatomy, and risk-stratifying patients with coronary artery disease. Preliminary studies have demonstrated its superiority over the the Synergy between percutaneous coronary intervention with Taxus and Cardiac Surgery (SYNTAX) score with respect to outcome predictions for acute myocardial infarction (AMI) patients. However, there are fewer studies on the prognostic in chronic coronary artery disease(CAD). This study aimed to clarify whether the CatLet score had a predictive value for in-stent restenosis(ISR) in patients with chronic coronary artery disease undergoing percutaneous coronary intervention with drug-eluting stent(DES). Methods A total of 260 patients who were diagnosed with chronic CAD and underwent coronary DES implantation at the second affiliated Hospital of Wannan medical college in China were consecutively enrolled from January 2020 to June 2021.Finally, 164 patients underwent the second angiography after 2 years.According to whether ISR was detected at follow-up angiography, patients were divided into the ISR group (n = 26) and the non-ISR group (n = 139). Results A total of 165 patients (46 women and 119 men) with a mean ages of 66.19 ± 10.54 years were finally enrolled in this study. Of these, ISR occurred in 26/165 chronic CAD patients (15.76%) by follow-up angiography. Univariate analysis showed that most baseline characteristics of the ISR and non-ISR group were similar. Patients in the ISR group had significantly the history of chronic obstructive pulmonary disease(COPD), adverse lesion characteristic, higher Catlet score compared with patients in the non-ISR group.The CatLet score was capable of predicting in-stent restenosis after adjustment for risk factors; The Multivariable-adjusted model showed good calibration and good discrimination (area under ROC curve = 0.7164) for ISR. Conclude CatLet score is a new predictor of ISR in patients with chronic CAD after coronary DES implantation.